The Web of Meaning : The Internet in a Changing Chinese Society - Yuan, Elaine J., 1974- (Book collections on Project MUSE., 2021)
"Taking off at the height of China's socioeconomic reforms in the mid-1990s, the Internet developed alongside the twists and turns of the country's rapid transformation. Central to many aspects of social change, the Internet has played an indispensable role in the decentralization of political communication, the expansion of the market, and the stratification of society in China. Through three empirical cases--online privacy, cyber-nationalism, and the network market--this book traces how different social actors engage in negotiation of the practices, social relations, and power structures that define these evolving institutions in Chinese society. Examining rich user-generated social media data with innovative methods such as semantic network analysis and topic modeling, The Web of Meaning provides a solid empirical base for critiquing the power relationships that are embedded in the very fiber of Chinese society."--